A history of data visualization and graphic communication - Friendly, Michael, 1945-; Wainer, Howard, 1943- (Cambridge MA ; London : Harvard University Press, 2021)
"Statistical graphing was born in the seventeenth century as a scientific tool, but it quickly escaped all disciplinary bounds. Today graphics are ubiquitous in daily life. Michael Friendly and Howard Wainer detail the history of data visualization and argue that it has not only helped us solve problems, but it has also changed the way we think"--
In the beginning... -- The first graph got it right -- The birth of data -- Vital statistics: William Farr, John Snow and cholera -- The big bang: William Playfair, the father of modern graphics -- The origin and development of the scatterplot -- The golden age of statistical graphics -- Escaping Flatland -- Visualizing time and space -- Graphs as poetry.
Includes bibliographical references and index (p. [293]-308).
Keywords: Information visualization -- History; Visual communication -- History; Graphic methods -- History; Visual analytics -- History